2015
DOI: 10.3906/bot-1405-16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture media and carbon sources on biomass productivityand oil content of the algae Sirogonium sticticum, Temnogyra reflexa,Uronema elongatum, and Chroococcus turgidus

Abstract: seeds contain oil in extractable quantities. Therefore, algae appear to be the cheapest source among all the renewable sources for biodiesel production. Green microalgae contain 20% to 70% lipid and exhibit extraordinary potential for cultivation as energy crops (Xu et al., 2006;de Vries et al., 2010). They do not need arable land for cultivation and can be grown in industrial, municipal, and agricultural effluents, and fresh-and seawater (Chinnasamy et al., 2010). The growth and oil producing efficiency of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The composition of this media was correlated with the requirements of our selected species and enhanced its growth. Similar results were recorded by Alam et al (2015). They selected four algal species and studied their growth in BM soil media.…”
Section: Screening Of Algal Speciessupporting
confidence: 63%
See 1 more Smart Citation
“…The composition of this media was correlated with the requirements of our selected species and enhanced its growth. Similar results were recorded by Alam et al (2015). They selected four algal species and studied their growth in BM soil media.…”
Section: Screening Of Algal Speciessupporting
confidence: 63%
“…A-Z media (Prescott, 2007) 2. Bristol's media (Alam et al, 2015 ) 3. Bristol's soil media (Bristol media along with 10g soil)…”
Section: Culture Media For Algal Biomassmentioning
confidence: 99%
“…Despite relatively high concentration of inorganic carbon in the inlet, at the outlet the inorganic carbon concentration was always low, with maximal values of 90 mg•l -1 , analogous to that found in natural seawater or freshwater sources, so exhausted culture broth being acceptable for safe releasing to environment. It has been reported that using wastewater the organic carbon contained on these effluents can enhance the productivity of microalgae cultures by favouring mixotrophic and including heterotrophic growth (Alam et al, 2015). However, based on the values here reported this fact don't take place when using centrate as nutrients source including at high percentages at which the cultures are stressed by excess of ammonium.…”
Section: Nutrient Removal Capacity and Strippingmentioning
confidence: 52%
“…Stressor also can become a factor for slow developmental of P. orientalis. Minimization of stressors factors with a combination of quality algae diets led to faster gonadal development and directly faster the maturation of P. orientalis [30]. It is shown that the physico-chemicals parameters at the study sites were compatible for the algal growth where the temperature was between 30 o C -34 o C, salinity between 20 o C -29 o C, and pH between 8 -8.5.…”
Section: Resultsmentioning
confidence: 91%
“…Nutrient content in soil and water may affect the quality of microalgae. Carbon for example, may enhance the lipid production of microalgae [30]. Nitrogen serves as important element for the growth and formation of protein and nucleic acid in algal cell.…”
Section: Resultsmentioning
confidence: 99%